Moderate Hyperthermia Induces Apoptosis in Metaphase-Arrested Cells But Not in Interphase Hela Cells - Paulson, James R.; Kresch, Agnes K.; Mesner, Peter W. (Scientific Research Publishing, 2016)
Metaphase-arrest agents and hyperthermia are both known to be capable of inducing apoptosis, and they have been used, separately, in cancer treatments. Here, we have examined whether the two treatments together may have a synergistic effect. We find that when H-HeLa cells are arrested in metaphase with spindle poisons (nocodazole or paclitaxel) and then subjected to mild heat treatment (41.5℃), they exhibit morphological changes typical of apoptosis within three hours. Moreover, those changes are blocked by the pan-caspase inhibitor zVAD-fmk, indicating apoptosis, and activated Procaspase 3 is detected by immunoblotting and by staining with the fluoresce-in-labelled caspase inhibitor FAM-VAD-fmk. Interphase cells treated in the same way do not under-go apoptosis, even with spindle poisons present. Induction of apoptosis is more rapid when the cells have been arrested longer in metaphase, suggesting that accumulation or depletion of some cellular component(s) during metaphase-arrest may make them more susceptible to hyperthermia. Further work is in progress to test whether other cell lines exhibit the same behavior and to learn more about the mechanism. The phenomenon is of interest because it may provide clues to how hyperthermia induces cell death and may yield novel therapeutic approaches to block or stimulate apoptosis.
Keywords: Apoptosis; Caspase; Heat Treatment; H-Hela; Hyperthermia; Metaphase-Arrest; Mitosis; Nocodazole; Paclitaxel; zVAD-fmk